Administrative Reform in Mahakam Ulu Regency in the Context of Supporting Border Area Development - Albertus Lung; Reza Fathurrahman (Dinasti Publisher, 2024)
Administrative reform is a demand that the Indonesian Government must carry out in organizing government. Various aspects of state management are required to undergo improvement. With the development of the existing paradigm, the essence of administrative reform also targets border areas. The reason is that the border region is an area that has a strategic position and role in maintaining the existence of the nation and state. After the expansion of East Kalimantan Province with the formation of North Kalimantan Province, the only state border area in East Kalimantan Province is currently in Mahakam Ulu Regency. As a state border area with open gates, Mahakam Ulu Regency certainly has a geostrategic and geopolitical role that is worth taking into account. Based on a literature review, this article analyzes administrative reform in Mahakam Ulu Regency in supporting the development of Mahakam Ulu as a border area. The research results show that administrative reform has a very priority place in efforts to support development in Mahakam Ulu Regency. Administrative reform within the Mahakam Ulu Regency Government includes strengthening institutions, strengthening the HR management system, strengthening performance accountability, strengthening governance, strengthening the supervision system, and improving public services. Government officials are also required to master various applications and systems that are built to simplify and transparently carry out their duties, develop ASN competencies, monitor and evaluate, and support village governments. All administrative reform commitments are supported by the political will of the Regent of Mahakam Ulu himself.